Approaches to congenital syphilis (Research, Society and Development, 2020)
Introduction: The following work deals with congenital syphilis as a central theme, addressing its understandings and results. Objective: To define the scope of congenital syphilis by analyzing the performance of nursing in prenatal care. Methods: This study, in the form of scientific research, is the result of an analysis of theoretical framework, carried out from April to November 2019, through consultation of scientific articles through electronic databases and publications of health journals ; regulations of the Ministry of Health and virtual libraries. Results: through the practical and theoretical framework verified, it is considered that Syphilis is an impacting factor in the health of adults and children around the world, as well as the various Sexually Transmitted Infections. The growing number of cases of contagion of this disease has alarmed the World Health Organization, which, in turn, has been encouraging actions to combat contagion, insisting on passing on quality information and on the action of health professionals in preventing, diagnosing and in the treatment of the disease. In this sense, the performance of the nursing professional during the prenatal period significantly helps the health of the pregnant woman, the partner and the baby, in order to promote the complete performance of the prenatal care, an indispensable tool in guaranteeing health during the gestational period.